A Quantitative Approach to Challenges Facing Online and Physical Classes in Social Studies Learning Higher Education - Omolaf, BABALOLA Ebenezer; Ize, OLUDARE Precious (Jurnal Pendidikan Ilmu Sosial, 2022)
The aim of this research is to investigate the challenges faced by online and physical classes in social studies learning in higher education. This condition causes differences in online or physical face-to-face classes. Descriptive research of the survey type was employed to achieve the purpose of this study. Students in five randomly selected faculties in University of Ilorin, Nigeria made up the study target population. In order to choose sample from each of the selected faculties, proportionate sampling procedure was used. The actual sample size for the study was 200 Undergraduates, who were chosen using random selection techniques. Descriptive statistics of mean score were used to analyse the information obtained from the respondents. The findings of this study shows that students faced challenges while learning in both online and physical classrooms. It was concluded that despite the underlying similarities between online and physical classroom, the two modalities are very different from one another. Online teaching is typically student-centered which necessitates active learning, in contrast to traditional classroom instruction, which has been known to be teachers-centered and call for passive learning. It was a challenge for teachers to move from face to face in class mode to virtual learning, changing their teaching methodologies, and managing their time. And it was also a challenge to develop content which did not only covers the curriculum but also engage the learners.